A SEDIMENTABLE COMPONENT OF ALLANTOIC FLUID AND ITS RELATIONSHIP TO INFLUENZA VIRUSES - Knight, C. A. (The Rockefeller University Press, 1944)
Macromolecular material was isolated from normal allantoic fluid by a centrifugation procedure comparable to that currently employed for the concentration and purification of influenza viruses. The yield of material was found to vary with the age of the embryo, reaching a maximum average value after 14 days of incubation at 39°C. of about 0.02 mg. per ml. of allantoic fluid. The purified material was found to contain protein, carbohydrate, and lipid and to have a general composition similar to purified preparations of PR8 influenza virus. A typical preparation of normal material had an isoelectric point at pH 2.3. Sedimentation studies indicated that the normal material can give a variety of sedimentation constants depending upon the concentration and viscosity of the preparations. The sedimentation constant, corrected for viscosity, of the major component of a fresh preparation was 170 S. The diameters of the predominant particles shown in electron micrographs of the normal material and of preparations of PR8 influenza virus were about 40 and 100 mµ, respectively. Serological tests indicated that the normal material is a good antigen and that preparations of both A and B types of influenza virus obtained from allantoic fluids by centrifugation show a strong serological relationship to the normal material. Freezing and thawing of allantoic fluid, and repeated adsorption of virus on red cells, failed to provide a practical basis for the separation of normal protein from the virus entity in the case of PR8 virus. In the cases of similar preparations of F12 and of Lee viruses, a partial separation of a small component was accomplished by fractional centrifugation and this component and the normal protein were shown to be identical or very closely related. Antiserum to the purified normal material inhibited red cell agglutination by A and B types of influenza virus at serum dilutions of 600 to 700, but failed to show significant neutralizing capacity in chick embryo and in mouse tests at a serum dilution of 100. Rabbit antiserum to purified preparations of PR8 virus gave a 50 per cent red cell agglutination inhibition endpoint at a serum dilution of 112,000. Some of the implications of the findings are discussed.